Etika Kerja pada “Biro Keuangan Universitas Nusa Nipa Maumere” - Mariabel Carcia, Maria Silvana; Chrispina, Elisabeth Melania; Nona Fani, Fransiska; Regi, Yonitha; Wohen, Yusni Nona; Gewar, Yeremias Blatan (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Ethics in this day and age is a benchmark for human behavior, both in daily life and in the world of work. Work ethics is a set of values, norms, and moral principles that guide an individual's behavior in a work environment. It covers a wide range of aspects. The research approach used is qualitative with a descriptive method. This approach aims to describe in depth the work ethics practices applied to the Finance Bureau of Nusa Nipa Maumere University. The practice of cooperation among employees is also seen to be significant in creating a harmonious working atmosphere. Moments like cleaning up the office together show that collaboration and mutual respect among colleagues can improve team bonding. Additionally, open communication between employers and employees creates a supportive environment, where each individual feels valued and motivated to give their best in their jobs.